2008
DOI: 10.1002/pds.1679
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric drug surveillance and the food and drug administration's adverse event reporting system: an overview of reports, 2003–2007

Abstract: This overview highlights the need for strengthening the passive drug surveillance system from a pediatric perspective, as well as investing in more active surveillance systems. Drug safety initiatives to better capture risk information in order to balance the risk/benefit of drug use in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 5 publications
1
15
1
Order By: Relevance
“…The number of AE reported in children has been growing since 2008. A 2009 study reported a flat trend from 2003 to 2007 in AEs reported to the FDA for children (mean 7248 reports/yr) . However, we found that the number of AEs increased from 12,100 in 2008 to 21,227 reports in 2011 (data not shown).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…The number of AE reported in children has been growing since 2008. A 2009 study reported a flat trend from 2003 to 2007 in AEs reported to the FDA for children (mean 7248 reports/yr) . However, we found that the number of AEs increased from 12,100 in 2008 to 21,227 reports in 2011 (data not shown).…”
Section: Discussioncontrasting
confidence: 59%
“…Like us, these investigators also found ADHD drugs and antiepileptics to be the most common categories of medications among AE reports in children. Another group using the FAERS database in 2003–2007 reported that ADHD medications, antiepileptics and antipsychotics were the top drug classes associated with AEs in children aged 2–10 years and in adolescents 11–16 years of age . Additionally, the ADHD medication atomoxetine has been found to be among the most commonly reported drugs associated with AE in children aged 0–17 years, based on an analysis from the WHO global individual case safety report database (Vigibase) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, an overview of ADRs reported to the FDA’s Adverse Event Reporting System revealed that the number of pediatric reports to the Adverse Event Reporting System over the past 5 years has remained steady (Figure 1), while reports for adults have increased fivefold over the same time period. The authors concluded that improvement in the passive surveillance system is needed from a pediatric perspective, and recommended that investments be made in active surveillance systems to better capture risk information in children [14]. …”
Section: Adr Reporting In Children: General Considerations and Challengesmentioning
confidence: 99%
“…The result is a potential delay in the authorisation of antibiotics for children and a consequent increase in off-label prescribing [5]. Moreover, given the paucity of information of new antibiotics in children, data on drug safety and tolerability are often extrapolated from adult studies, with the consequent risks of underestimating toxicity, inadequate dosages and clinical failures [6].…”
Section: Introductionmentioning
confidence: 99%